2020
DOI: 10.1002/jsfa.10884
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the extract from peanut meal fermented with Bacillus natto and Monascus on lipid metabolism and intestinal barrier function of hyperlipidemic mice

Abstract: BACKGROUND Hyperlipidemia is one of the metabolic disorders that poses a great threat to human health. This study is aimed at investigating the potential hypolipidemic properties of extract from peanut meal fermented with Bacillus natto and Monascus in mice fed with a high‐fat diet. Herein, 60 male C57BL/6J mice were randomly divided into six groups: four control groups, comprised of a normal group, a model (M) group, a positive control group (atorvastatin 10 mg kg−1), and a nonfermented peanut meal extract gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In addition, microvilli are attached to the surface of the intestinal mucosa, which can increase the intestinal surface area and promote the digestion and absorption of nutrients in the small intestine (Oh & Yoo, 2019). We observed that HFD caused intestinal villus shortening and villus shedding in rats, which was consistent with the previously reported effect of HFD on intestinal absorption in mice (Lu et al, 2021). However, JLCC513 intervention could improve the absorption function of the small intestine and maintain intestinal health by changing the morphology and structure of the intestinal mucosa.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, microvilli are attached to the surface of the intestinal mucosa, which can increase the intestinal surface area and promote the digestion and absorption of nutrients in the small intestine (Oh & Yoo, 2019). We observed that HFD caused intestinal villus shortening and villus shedding in rats, which was consistent with the previously reported effect of HFD on intestinal absorption in mice (Lu et al, 2021). However, JLCC513 intervention could improve the absorption function of the small intestine and maintain intestinal health by changing the morphology and structure of the intestinal mucosa.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that dairy products fermented by probiotics have good hypolipidemic function in vivo , and clinical studies have found that a variety of probiotics can effectively regulate lipid metabolism 11 . Bacillus subtilis natto , as an acid‐resistant and heat‐resistant beneficial bacterium, can inhibit the growth of spoilage bacteria and pathogenic bacteria, maintain intestinal balance, and promote intestinal health 12 . Peanut meal is a by‐product of peanut oil, and Liu et al 13 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Bacillus subtilis natto, as an acid-resistant and heat-resistant beneficial bacterium, can inhibit the growth of spoilage bacteria and pathogenic bacteria, maintain intestinal balance, and promote intestinal health. 12 Peanut meal is a by-product of peanut oil, and Liu et al 13 found that peanut peptides have a good ability to adsorb cholesterol. After fermentation by B. natto, the contents and utilization rates of bioactive components such as peptides and polysaccharides in peanut meal were significantly increased, and some beneficial microorganisms and bioactive substances in the fermentation could reach the intestinal tract and could improve the intestinal microecological balance, thereby preventing the occurrence of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that the angiotensin‐converting enzyme inhibitors (ACEI) and antioxidants were presented in pigeon pea fermented by B. natto (Lee et al, 2015). B. natto and its fermented food have been proved to play an essential role in improving cardiovascular and cerebrovascular diseases and obesity (Lu et al, 2021; Vaithilingam et al, 2016). Moreover, soybeans are rich in protein, unsaturated fatty acids, soy saponins, isoflavones, and dietary fiber, which could also promote weight loss (Chen et al, 2019; Hwang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%